Preparation And Characterization Of Cross Linked Chitosan Filled Chitosan Composites - Julkapli, Nurhidayatullaili Muhd (2012)
The interfacial bonds, homogeneity and rigidity of filler are the two main criteria that significantly influenced the mechanical, thermal and hydrophilicity of the chitosan (Cs) based bio-composites. Therefore, the aim of this study was to investigate the role of cross linked chitosan (XCs) as filler in the Cs matrix towards the interfacial, homogeneity and rigidity of the produced Cs bio composites. XCs was synthesized using three different cross linking agents named as 1,2,4,5-benzentetr carboxylic (BT), 4,4’-oxydiphtalic anhydride (ODA) and 3,3’,4,4’-diphthalic anhydride (DPA) which consequently produced three different types of XCs filler; 1,2,4,5-benzentetra carboxylic-chitosan (BTC), 4,4’-oxydiphtalic anhydride-chitosan (ODAC) and 3,3’,4,4’- diphthalic anhydride-chitosan (DPAC).